Horizontal methods for molecular biomarker analysis. Methods of analysis for the detection of genetically modified organisms and derived products. Construct-specific real-time PCR method for detection of P35S-pat-sequence for screening for genetically modified organisms Part 3, (8th July 2020) - British Standards Institution,
No abstract available